2021
DOI: 10.13075/ijomeh.1896.01733
|View full text |Cite
|
Sign up to set email alerts
|

Evidencing the influence of pre-pandemic sports participation and substance misuse on physical activity during the COVID‑19 lockdown: a prospective analysis among older adolescents

Abstract: Objectives: The physical activity level (PAL) has significantly decreased as a result of the social distancing and lockdown related to the COVID-19 pandemic, but there is a lack of knowledge on the correlates of PAL during the pandemic. The aim of this research was to examine the influence of pre-pandemic sports participation and substance use and misuse (SUM) on PAL during the COVID-19 pandemic. Material and Methods: The study included 661 high-school students from Bosnia and Herzegovina (aged 15-18 years, 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…Similarly, Spanish adolescents presented decreases in both moderate and vigorous PAL by 29.5% and 18.3%, respectively, during the lockdown [6]. Reduced PAL and increased sedentary behavior were confirmed in adolescents from Australia, Canada, Spain, Italy, and Germany [4,[7][8][9][10][11][12]. Results from studies conducted on adolescents from Croatia, and Bosnia and Herzegovina evidenced decreased PAL as a consequence of restrictions related Healthcare 2021, 9, 681 2 of 9 to the COVID-19 pandemic [13][14][15][16].…”
Section: Introductionmentioning
confidence: 72%
“…Similarly, Spanish adolescents presented decreases in both moderate and vigorous PAL by 29.5% and 18.3%, respectively, during the lockdown [6]. Reduced PAL and increased sedentary behavior were confirmed in adolescents from Australia, Canada, Spain, Italy, and Germany [4,[7][8][9][10][11][12]. Results from studies conducted on adolescents from Croatia, and Bosnia and Herzegovina evidenced decreased PAL as a consequence of restrictions related Healthcare 2021, 9, 681 2 of 9 to the COVID-19 pandemic [13][14][15][16].…”
Section: Introductionmentioning
confidence: 72%
“…The majority of studies noted a significant reduction in PA during the Covid-19 lockdown ( n = 32). In contrast, only few studies found an increase in PA ( n = 5) [ 57 , 72 , 84 , 100 , 109 ] while six studies failed to detect any changes in PA [ 50 , 51 , 68 , 71 , 86 , 99 ]. Fourteen other studies showed both, a decrease and an increase in PA, depending on the PA characteristics under study.…”
Section: Resultsmentioning
confidence: 99%
“…The 16 studies examined a total of 11,484 (5587 females) participants (one did not provide information on gender [ 53 ]) with an age range from four to 18 years [ 85 , 86 ]. Alonso-Martinez et al [ 69 ] were the only researchers who solely used device-based measurements, and Munasinghe et al [ 63 ] and Nyström et al [ 57 ] used both, SR and DB measurement methods.…”
Section: Resultsmentioning
confidence: 99%
“…The participants from Group 3 (with the greatest relative decline in PAL) were considered the "high-risk group," Group 2 was considered the "medium-risk group," and Group 1 was considered the "low-risk group" with regard to a decrease in PAL over the study period. Such categorization allowed us to calculate the multinomial regression for PAL∆% as a criterion, as recently suggested [31].…”
Section: Variablesmentioning
confidence: 98%